CEU Graduation Ceremony 1999 - Václav Havel's Speech
Recording of the CEU Graduation Ceremony of 1999. Part VI. The outgoing President and Rector Josef Jarab presents President Václav Havel with the Open Society Prize. After receiving the Prize from George Soros, President Václav Havel delivers the Commencement Address to an audience including members of the Budapest diplomatic community and numerous other prominent guests, in addition to the university's students, faculty and staff. The recording ends with the last parts of the ceremony: moving the tassel, the recessional and the reception.